PENGARUH PENGGUNAAN PEMBAYARAN DIGITAL (QRIS) TERHADAP TINGKAT PENGELUARAN KONSUMSI MAHASISWA ERA GENERASI Z DENGAN PERILAKU GAYA HIDUP MASA KINI - Adinda Ranandhea Nuhran; Risdayanti Ramli; Yonathan Luhat (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
This research aims to find out how transactions are implemented and what obstacles occur in using QRIS-based Payment Gateway Technology among today's Generation Z students. This research uses descriptive qualitative methods. The data collection techniques used are observation, interviews, and documentation which will later be processed through data analysis to answer the problem formulation. The research results show that (1) The implementation of QRIS-based payment gateway transactions among today's students continues to increase from October 2021 to January 2022, (2) There are still many obstacles in realizing the implementation of QRIS-based payment gateway transactions, (3) There are still many initiatives What has been done to overcome the problems with the QRIS (Quick Response Code Indonesian Standard) application is by uploading articles regarding the QRIS application on the official website of Bank Mandiri Persero tbk. Based on the list of developments in QRIS values, there was an increase in values from the following month. This means that the use of QRIS is in demand among today's generation Z students. Because it is considered easier to pay for purchase transactions, just by scanning the QRIS, students can make purchases. The supplier does not need to bother preparing refunds for purchase transactions. Purchase transactions are also considered more hygienic. Because it does not come into contact with banknotes from community to community. But even though using the QRIS application is more practical for students in the current generation Z era, the QRIS application cannot necessarily be used in the previous generation era. Most people in the previous generation preferred to use currency because they didn't have to bother opening an application and having to have a data package just to pay for groceries that weren't considered to be worth too much.